Simultaneous involvement of lungs, larynx and middle ear by tuberculosis -a rare case (Journal of Dhaka National Medical College & Hospital, 2012)
Simultaneous involvement of lungs, larynx and middle ear by tuberculosis is very rare. We present a rare case of simultaneous involvement of larynx and ear in a patient with pulmonary tuberculosis. A 17 years old male presented with fever and cough for 8 months, bilateral deafness for 5 months and hoarseness of voice for 3 months. The patient gave history of anorexia and progressive weight loss and history of close contact with tuberculosis patient. There were coarse crepitations on auscultation of both lungs. Indirect laryngoscopy revealed diffuse nodular swelling as well as thickening of the vocal cords. Examination of both ears revealed pale-yellow granulation tissue. ESR was 94 mm in 1st hour and chest radiograph showed diffuse patchy opacities extending over both lung fields. The results of two sputum examinations showed numerous acid-fast bacilli Histopathologic examination of punch biopsy from right and left ear lesions and biopsy tissue from laryngeal lesion taken by endoscopic instrument revealed granulomatous inflammation histologically consistent with tuberculosis.The patient responded well and promptly to the antituberculous therapy. The aim of this article is to create an awareness of Ear Nose Throat tuberculosis and to consider tuberculosis in the differential diagnosis of ear and laryngeal diseases and to emphasize the need for prompt recognition and treatment. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12195 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 53-55